Students Activities in Learning Pythagoras Theorems Using Desmos Application - Wulandari, Hilaria Yesieka Ayu; Siswono, Tatag Yuli Eko (Journal of Mathematical Pedagogy (JoMP), 2023)
This study aims to describe the creative thinking skills of students in solving problems related to the Pythagorean Theorem using Desmos application. This descriptive research involved 3 Junior High School students in grade 9 in Sidoarjo (Indonesia) who each had high, medium, and low ability backgrounds. The task in the form of questions consisted of two questions asking students to create two different triangles. The results of the analysis showed that high-ability students were able to create two different triangles if they were given sides 3 and 4 in the form of a right triangle and an equilateral triangle. Students with moderate and low abilities were able to draw right triangles with Desmos, but had difficulty drawing isosceles triangles. Both of them drew an isosceles triangle, but with side lengths of 3, 4, and 6. These results illustrate that the use of Desmos helps students' ideas in finding answers in drawing triangles, but the basic abilities that students have can be an obstacle in completing the given tasks.